Management Capabilities and Performance of Firms in the Russian Federation - Grover Goswami, Arti; Torre, Ivan (World Bank, Washington, DC, 2019)
Using the management and operational practices survey in the Russian Federation, this paper finds that an average Russian manufacturing firm adopts 43 percent of the structured management practices (a score of 0.43), a value that is far from the frontier (for example, the United States scores 0.62). This average mask the wide heterogeneity in practices, where a large share of firms adopt few structured management practices and only 3.5 percent of them have a score over 0.75. Consistent with the findings in other countries, better managed firms in Russia show stronger firm performance, measured as gross revenue per employee, value added per employee, total factor productivity, and employment growth. Improving the management score from the 10th to the 90th percentile is associated with an increase in sales per worker by 87 percent, value added per worker by 30 percent, and total factor productivity by 13.5 percent. What drives better management capabilities? Russian firms are similar to those in other countries, such that exporters and firms with foreign linkages are better managed. Switching from operating purely in the domestic market to being globally linked is associated with a significant increase in management capabilities. However, unlike the results in other countries, management capabilities in Russia are not associated with firm age, implying that firms do not learn to be better managed over their life cycle. This result points to the possibility of inefficient allocation of resources, such that learning and selection mechanism does not weed out the badly managed firms, perhaps due to the lack of pro-competitive forces.